2009
DOI: 10.1180/minmag.2009.073.3.495
|View full text |Cite
|
Sign up to set email alerts
|

The morphologies and compositions of depleted uranium particles from an environmental case-study

Abstract: Uraniferous particles from contaminated environmental samples were analysed by scanning electron microscopy with energy dispersive X-ray analysis (SEM-EDXA) and microfocus extended X-ray absorption fine structure (mEXAFS) spectroscopy. The particles of interest are uranium oxides, which were released into the environment by the combustion of scrap depleted uranium (DU) metal at a factory in Colonie, New York, USA. Most of the identified particles appear to have primary, 'as emitted' morphologies; some have evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…Examination of contaminated soils and dusts reveals primary uranium oxide particles in the size range 0.5 -150 µm, including mixed UO 2+x and U 3 O 8 spheres with diameters 20 -64 µm, and rarely secondary uranium precipitates (Chapter 3 / Lloyd et al 2009b). These spheres and other specific particle morphologies are directly comparable to those from munitions.…”
Section: Site Historymentioning
confidence: 66%
See 2 more Smart Citations
“…Examination of contaminated soils and dusts reveals primary uranium oxide particles in the size range 0.5 -150 µm, including mixed UO 2+x and U 3 O 8 spheres with diameters 20 -64 µm, and rarely secondary uranium precipitates (Chapter 3 / Lloyd et al 2009b). These spheres and other specific particle morphologies are directly comparable to those from munitions.…”
Section: Site Historymentioning
confidence: 66%
“…However, the Colonie soils are generally well-drained, and at least for oxidation in air, kinetics and surface passivation may limit bulk oxidation beyond UO 2+x (s) (McEachern & Taylor 1998), as appears to be the case for a few primary particles recovered from Colonie soils (Chapter 3 / Lloyd et al 2009b). Schoepite has a solubility three orders of magnitude greater than UO 2+x (Ragnarsdottir & Charlet 2000), therefore speciation is significant for contaminant transport and bioaccessibility.…”
Section: Lloydmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The transport of DU particles will depend on particle properties (i.e., size and density) and on prevailing meteorological conditions. 51 54,55 investigated the dispersion of aerosols formed during the combustion of waste metal at a uranium and DU processing factory in Colonie (NY, USA). The distribution of the DU aerosol was controlled by prevailing winds, with DU contamination found up to 600 m from the factory.…”
Section: Processes and Factors Affecting Radionuclide Transport In Thmentioning
confidence: 99%
“…In particular, comparison of the morphology of precipitates with those of subsequent calcination products suggests that microstructures of the precursor precipitates are retained through heat treatment [6][7][8][13][14][15][16]. A number of studies have shown that U 3 O 8 , a common intermediate in the production of nuclear material, generates schoepite phases (UO 3 ÁxH 2 O) during storage under higher relative humidities presumably following oxidation and/or hydration [2,[17][18][19]. It would be valuable to understand the variables contributing to temporally-induced morphology changes, and if any changes occur, the prospect for using the temporal changes in morphology that arise during storage under different conditions for forensic analyses.…”
Section: Introductionmentioning
confidence: 98%